Spatio-temporal connectivity and dispersal seasonal patterns in the Adriatic Sea using a retention clock approach - Nadal, Irene; Picciulin, Marta; Falcieri, Francesco M.; García-Lafuente, Jesús; Sammartino, Simone; Ghezzo, Michol (Frontiers in Marine Science, 2024)
Hydrodynamic features play a key role in determining the dispersal and connectivity of fish populations, especially in highly energetic areas determined by currents, river flow, and meteorologically induced fluctuations. Understanding how species interact with these physical processes is essential for managing vulnerable populations and identifying areas that require effective conservation efforts. This study examines the hydrodynamics that regulate connectivity in the Adriatic Sea, a shallow and semi-enclosed basin that is widely recognized as one of the most important areas in the Mediterranean Sea for protection. A high-resolution hydrodynamic model coupled with a lagrangian tracking module serves as the numerical tool. Lagrangian particles, representing eggs and larvae with typical biological characteristics of generic marine organisms inhabiting the region, are released throughout the basin at different times during a test year to identify the most likely pathways of individual dispersal. The temporal component of connectivity is highlighted using a previously developed retention clock matrix over different larval durations. Seasonality is a critical factor in dispersal, with greater variability and reduced efficiency in winter compared to summer. The potential implications of the results for improved assessment and management of high value marine species in the basin are discussed.